2021
DOI: 10.1017/jog.2021.35
|View full text |Cite
|
Sign up to set email alerts
|

A casting method using contrast-enhanced diethylphthalate for micro-computed tomography of snow

Abstract: Casting snow is necessary to prevent metamorphism and deformation prior to X-ray micro-computed tomography (μCT) imaging. Current methods are insufficient for large-scale field sampling of snow due to safety considerations associated with the casting medium and/or lengthy sample preparation times. Here, a casting method using contrast-enhanced diethylphthalate (DEP) for μCT of snow is presented. The X-ray contrast of DEP is enhanced with barium titanate nanoparticles (BaTiO3) and iodine (I2). A partially unsup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Then the microstructure parameters such as specific surface area (SSA) were computed from the segmented images. It was shown that both of the methods were prone to hardware setup, but the energy-based (graph cut) method is not subjective to the choice of a human user and it benefits from local spatial information, with less affection of beam hardening [32]- [34].…”
Section: Introductionmentioning
confidence: 99%
“…Then the microstructure parameters such as specific surface area (SSA) were computed from the segmented images. It was shown that both of the methods were prone to hardware setup, but the energy-based (graph cut) method is not subjective to the choice of a human user and it benefits from local spatial information, with less affection of beam hardening [32]- [34].…”
Section: Introductionmentioning
confidence: 99%